The traumatic history of psychoanalysis - van Zyl, Susan (PINS-Psychology in Society, 2025)
Kuriloff , Emily A (2014) Contemporary psychoanalysis and the legacy of the Third Reich: History, memory, tradition. New York: Routledge. ISBN 978-0-415-88319-1 pbk. Pages xvi +177. In the final chapter of Contemporary psychoanalysis and the legacy of the Third Reich (2014), Emily Kuriloff refers to having asked psychoanalyst Jack Drecher whether he thought the field of psychoanalysis had been influenced by “the Shoah” (p143). The answer Kuriloff quotes, “How could psychoanalysis not have been influenced by its own history” may be, as she suggests, characteristically Jewish (in responding to a question with another one) but it is, of course, much more than that. How could the most terrifying genocide in living memory, directed to the extermination of the very people that gave rise to the description of psychoanalysis as “the Jewish profession”, have not influenced both the theory and practice of psychoanalysis in important ways?